Classroom Management Problems in the Pre – Professional Practices - Toaquiza Vega, Angel Fausto (2024)
Classroom management is a fundamental element in the teaching-learning process, since it stimulates the professionalism and commitment of future English teachers from their practicum in Educational Institutions, where they make their first approach to an educational reality and must guarantee an effective learning environment. The objective of this study is to identify the main classroom management problems in pre-professional teaching. For which, the research question is “What are the possible causes of the classroom management problems faced by pre-service English teachers?” In this context, the present research work is descriptive and qualitative approach. Furthermore, to obtain the information, a semi-structured interview was applied, which was validated by three professors from the Technical University of Cotopaxi. In this sense, the participants in this study were five students in the eighth semester of the Pedagogy of National and Foreign Languages (English) major at the Technical University of Cotopaxi-Campus Pujilí. After data collection, the analysis and discussion of the responses of each of the students coded as ST.1.2.3.4.5 was carried out. Based on the findings, the interviewees point out that the main problems arise from their limited knowledge and experience in classroom management prior to the execution of their pre-professional teaching, which prevents them from achieving good results in learning English for all students. Taking this into account, it is suggested to relocate the Classroom Management subject prior to the execution of pre-professional teaching, since precise knowledge of this subject plays an important role in ensuring the good performance of future English teachers in training.